The effects of membrane potential oscillations on the excitability of rat hypoglossal motoneurons - Zhang, Qiang; Dai, Yue; Zhou, Junya; Ge, Renkai; Hua, Yiyun; Powers, Randall K.; Binder, Marc D. (Frontiers in Physiology, 2022)
Membrane potential oscillation (MPO) induced by synaptic inputs and intrinsic ion channel activity play a role in regulating neuronal excitability, but the precise mechanisms underlying their contributions remain largely unknown. Here we used electrophysiological and modeling approaches to investigate the effects of Gaussian white noise injected currents on the membrane properties and discharge characteristics of hypoglossal (HG) motoneurons in P16-21 rats. We found that the noise-induced MPO facilitated spike initiation by hyperpolarizing the cells’ voltage threshold by 3.1+/-1.0mV and reducing the recruitment current for the tonic discharges by 0.26+/-0.1nA, on average (n=59). Further analysis revealed that the noise reduced both recruitment and decruitment currents by 0.26+/-0.13 and 0.33+/-0.1nA, respectively, and prolonged the repetitive firing. The noise also increased the slopes of frequency-current (F-I) relationships by 1.1+/-0.2Hz/nA. To investigate the potential mechanisms underlying these findings, we constructed a series of HG motoneuron models based on their electrophysiological properties. The models consisted of five compartments endowed with transient-sodium (NaT), delayed-rectify-potassium (K(DR)), persistent-sodium (NaP), calcium-activated-potassium (K(AHP)), L-typ- calcium (CaL) and H-current channels. In general, all our experimental results could be well fit by the models, however, a modification of standard Hodgkin-Huxley kinetics was required to reproduce the changes in the F-I relationships and the prolonged discharge firing. This modification, corresponding to the noise generated by the stochastic flicker of voltage-gated ion channels (channel flicker, CF), was an adjustable sinusoidal function added to kinetics of the channels that increased their sensitivity to subthreshold MPO. Models with CF added to NaP and CaL mimicked the noise-induced alterations of membrane properties, whereas models with CF added to NaT and K(DR) were particularly effective in reproducing the noise-induced changes for repetitive firing observed in the real motoneurons. Further analysis indicated that the modified channel kinetics enhanced NaP- and CaL-mediated inward currents thus increasing the excitability and output of HG motoneurons, whereas they produced relatively small changes in NaT and K(DR), thus balancing these two currents and triggering variability of repetitive firing. This study provided insight into the types of membrane channel mechanisms that might underlie oscillation-induced alterations of neuronal excitability and motor output in rat HG motoneurons.